Plastic in Arctic fox faeces of Iceland : studying the suitability of Arctic fox faeces analysis for plastic monitoring in Iceland - Technau, Birte, 1993- (2021)
Verkefnið er lokað til 01.06.2022. Plastic pollution in the marine environment is a growing concern in the Arctic and affects multiple marine and coastal organisms across trophic levels. The Arctic fox (Vulpes lagopus) is the only native terrestrial species in Iceland and could, as a monitoring species, provide an important insight into the state of the environment in the Arctic in terms of plastic pollution. In 2019 a study was commissioned by the Environment Agency, that reported plastics in Arctic fox stomachs (Skúladóttir, 2019). This thesis is in line with findings from this study and seeks to increase knowledge about the general state of plastic pollution in the Icelandic environment, and of the Arctic fox. In total 238 faecal samples were analysed; 80 faeces samples from the nature reserve of Hornstrandir in the Westfjords from the summer of 2020, 80 samples from Hornstrandir from 1999, and 78 samples from 2017-2018 from the northwest, the northeast and the southwest of Iceland. The aim of this study was to quantify plastic pollution in Arctic fox faeces in Iceland and compare findings of plastic in Arctic fox faeces in Hornstrandir in 1999 and 2020 as well as other regions in Iceland in 2017- 2018. Frequency of occurrence was determined for all three sample groups and was found to be similar in all three groups. The incidence rate of plastic and paper particles for all 238 samples was 5.04%, equalling 2 paper particles, 1 tar particle and 9 confirmed plastic particles in 238 samples. None of the samples contained more than one plastic item. Secondly, the highest average of mass and volume of plastic and paper particles were found in samples from 2020 in Hornstrandir, followed by samples from 2017-2018 from other regions in Iceland. Overall plastic occurrence was low and indicate that Arctic fox faeces analysis may not be an effective monitoring tool for plastic levels in Iceland. However, the ingestion rate of plastic of this species remains a serious concern and warrants further studies. Furthermore, ...